Optimisation of the liquid-liquid extraction of soybean oil using a binary mixture - Martins, Glêndara Aparecida; Peluzio, Joênes (Revista Ciência Agronômica, 2014)
The soybean has been widely studied due to its constituents and to their application. Authors have pointed out that its composition can vary, with its use frequently taking the form of oil. The oil extraction process, which is in constant application in the market, consists of the use of extraction solvents, with hexane being one of the most used; however the fact that this comes from non-renewable sources has aroused interest in its replacement. As a result, ethanol has been seen as an alternative solvent, despite increasing the cost of the process. This study therefore aims to evaluate the composition of three soybean cultivars planted in the region of Palmas, in the state of Tocantins, Brazil, and to optimise oil extraction from the beans through the use of a binary mixture of ethanol and hexane. The cultivars displayed high protein and lipid potential. The extraction time and temperature proved influential in the process. Ethanol, when present in greater quantity in the mixture, with an increase in temperature, caused an increase in the levels of extracted oil.